Simulation Of Passenger Flow And Waiting Time For International Departure Using Witness Horizon - Aza, Muhamad Farhan Husaini (Universiti Sains Malaysia, 2021)
Passenger flow will start from the departure hall until the flight departure. There are a few processes before a passenger take a flight which are check-in, boarding pass check, inspection and quarantine, security controls that divided into two x-ray machine and desks, sanitary inspection, departure passport control and flight. This research is to study about each process involved in one flow of passenger in international departure operation. The research is conducted with a collaboration with KXP AirportCity Holdings Sdn Bhd whom provide the data that of each process time and the various layout for in a departure hall. This research use Witness Horizon software to simulate and study every process that occurs. There are four model created to show the changed of time for every improvement. The passenger needs to arrive three hours before the departure. The research uses a flight Boeing 737-800 which can accommodates 168 passengers at one time. The four model are Model 1 is the automatic processes passenger flow, Model 2 is manual processes passenger flow, Model 3 involved of combination of automatic and traditional process and finally Model 4 is about adding more counter to reach the target time. Each model then was analysed to identify the best passenger flow that can be completed within three hours before departure. Based on the result, it can be concluded that Model 4 is the best model that can be used.